The covert struggle: Tuberculosis amidst silicosis cases - Maria Jose; Nagarjun S; Abi G; Sowmya P; Nalini Jayanthi Nagesh (Asian Journal of Medical Sciences, 2025)
Silicosis is a fibrotic lung disease that occurs due to the inhalation of respirable crystalline silicon dioxide, or silica, typically encountered in occupational settings. In countries where tuberculosis (TB) is prevalent, TB often coexists with silicosis and significantly increases the mortality rate among affected individuals. Educating workers in industries such as quarrying and sandblasting about the risks of occupational lung diseases is essential. This case series involves patients who presented to a tertiary care hospital with a history of occupational silica dust exposure. The study assessed their symptoms, medical history, and diagnostic workup. Patients who reported shortness of breath and cough, along with a history of prolonged exposure to silica, were included. Three of the silicotuberculosis cases had occupational risk factors such as stone cutting, work at construction sites, and borewell drilling. The final case developed silicosis due to chronic exposure to inorganic dust during activities such as tilling and plowing. Detailed histories and clinical examinations were recorded for all patients, who exhibited radiological signs consistent with silicotuberculosis. Although their sputum acid-fast bacillus smears were negative, sputum and bronchoalveolar lavage (BAL) GeneXpert tests confirmed the presence of TB. Anti-TB treatment was initiated for all four patients following microbiological confirmation. Active surveillance of workers exposed to silica, including spirometry, chest X-rays, and respiratory questionnaires, is vital both before and during employment. Workers involved in stone grinding and construction are at particular risk, as they are exposed to fine silica particles that commonly affect the distal airways and alveoli, leading to progressive massive fibrosis. This approach can substantially reduce the morbidity and mortality associated with silicotuberculosis. The use of respiratory masks and ensuring proper ventilation in the workplace are key preventive measures against the onset of silicosis.